Dispositivo de geo-localización de ganado bovino en entornos agropecuarios - Gutierres Sánchez, Juan Pablo (2021)
The objective of this titling work was to develop a geolocation device for the country's livestock sector, which allows determining the cattle location, in order to contribute to the prevention of cattle rustling and help farmers to quickly find cattle in the grasslands. This work was developed in 4 stages, in the first stage a SWOT analysis was carried out in order to have a complete diagnosis about the company and the environment that surrounds it. In the second stage, a market study was carried out, where the techniques of the interview and the survey were used in order to determine the population to which the product would be directed and the reception that it would have in the market. In the third stage, the bibliographic method was used to identify the alternatives for action that would provide a solution to the problem raised. Finally, in the last stage, financial methods were used to describe the economic viability of the business project to be developed. The result obtained is from a low-cost device that, through a mobile application, enables the location of cattle to be determined with a range of up to 7.5 kilometers away.